O Poder Simbólico e a Cooperação Portuguesa: Uma análise sobre o papel da língua - Bruna Martins; Rui da Silva; La Salete Coelho (Cadernos de Estudos Africanos)
This article aims to analyse and reflect on the role of the Portuguese language as a symbolic power system in the Portuguese Cooperation. This analysis is focused on the period between 1999 and 2019, based on the different documents published in this period. This article is in some extent a self-reflection, since the authors consider themselves as “critical friends” and not external observers of the Portuguese Cooperation. The article argues that the Portuguese language emerges as a symbolic power system that perpetuates coloniality relationships stemming from the fact that it is a soft power strategy from the Portuguese state, not a development objective.